Genome Sequencing and Comparative Genomics Analysis Revealed Pathogenic Potential in Penicillium capsulatum as a Novel Fungal Pathogen Belonging to Eurotiales - Yang, Ying; Chen, Min; Li, Zongwei; Al-Hatmi, Abdullah M. S.; de Hoog, Sybren; Pan, Weihua; Ye, Qiang; Bo, Xiaochen; Li, Zhen; Wang, Shengqi; Wang, Junzhi; Chen, Huipeng; et al. (Frontiers in Microbiology, 2016)
Penicillium capsulatum is a rare Penicillium species used in paper manufacturing, but recently it has been reported to cause invasive infection. To research the pathogenicity of the clinical Penicillium strain, we sequenced the genomes and transcriptome of the clinical and environmental strains of P. capsulatum. Comparative analyses of these two P. capsulatum strains and close related strains belonging to Eurotiales were performed. The assembled genome sizes of P. capsulatum are approximately 34.4 Mbp in length and encode 11,080 predicted genes. The different isolates of P. capsulatum are highly similar, with the exception of several unique genes, INDELs or SNP in the genes coding for glycosyl hydrolases, amino acid transporters and circumsporozoite protein. A phylogenomic analysis was performed based on the whole genome data of 38 strains belonging to Eurotiales. By comparing the whole genome sequences and the virulence-related genes from 20 important related species, including fungal pathogens and non-human pathogens belonging to Eurotiales, we found meaningful pathogenicity characteristics between P. capsulatum and its closely related species. Our research indicated that P. capsulatum may be a neglected opportunistic pathogen. This study is beneficial for mycologists, geneticists and epidemiologists to achieve a deeper understanding of the genetic basis of the role of P. capsulatum as a newly reported fungal pathogen.